Pengaruh Suhu Tumbukan pada Campuran Aspal Beton dengan Jenis Lapis AC-WC Gradasi Halus - Wahyudi, Wahyudi; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study was conducted to determine the effect of temperature on the Marshall parameterscompaction to mix AC - WC subtle gradations central limit. Optimum Asphalt Content Value(KAO) in the study sought to use 15 samples and done in the laboratory of Highway University ofLampung. From the analysis of the Marshall parameters obtained KAO mixture is 5.7%. Marshallparameter data retrieval is done twice trials, each experiment using 2x24 samples with the sametreatment for each experiment. Compaction temperature is 120 o C-155 o C is reviewed by varasi5 o C.From the results of experiments that have been conducted, Marshall parameter valuesobtained in experiment 1 and experiment 2 is not too much different. In general, the Stability,Flow, VMA and VFA qualify specifications bina marga 2010, the MQ does not meet thespecifications of 135 o C or lower temperatures and VIM value does not meet the specifications of130 o C or lower temperatures.Based on the tendency of marshall parameter values obtained fromexperiment 1 and experiment 2 indicate that the data obtained from these experiments hasparticularly a small false possibility.Keywords: AC-WC, KAO, Marshall parameter, temperature compaction,